منهج ابن باديس في تنزيل آيات الدعوة على الواقع من خلال تفسيره "مجالس التذكير": الآية 125 من سورة النحل أنموذجاً: Ibn Badis’ Approach in Applying the Verses of the Call on Reality Through His Interpretation “Assemblies of Remembrance”: Surat An-Nahl:125 as a Model - Mahyuddin Hashim; Samia Baggash Al Hammadi (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Algeria witnessed a very critical time during the French colonial period, which prompted Ibn Badis, the one called as revivifier and reformer of his era, to look for solutions to the issues of his period. Ibn Badis resorted to the holy Qurʾān and designated his life to serve the book of Allah, interpreting and contemplating it, as well as extracting and deducing all regulations and provisions, applying them to his daily life. He also ensured proper installation of verses of the Qurʾān to act as a solution to various issues, including spreading the message of Allah and informing people about Him. This article introduces Ibn Badis and shines a light on how he implemented and used his understanding of Qurʾānic verses to solve his daily life issues, specifically his journey of advocating and guiding people towards getting to know Allah. The paper employed inductive and descriptive analysis to achieve this goal and concluded that Ibn Badis is a pioneer of reform and uplifted his society using Qurʾānic verses. He was greatly interested in the advocacy aspect (getting people to know Allah) of interpreting the Qurʾān verses, where he extracted the advocacy rules, etiquettes of the advocator and then implemented them in his everyday life.